ANALISIS KUANTITAS TROMBOSIT TERHADAP PEROKOK AKTIF DAN PEROKOK PASIF PADA MAHASISWA POLITEKNIK MEDICA FARMA HUSADA MATARAM - Musparlin Halid (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2022)
Platelets are one of the components of blood that have a major function in blood clotting. When the platelet level is above the normal range (> 400,000/microliter of blood) it is called thrombocytosis. When the platelet level is below the normal range (<150,000/microliter) it is called thrombocytopenia. This study aims to analyze the number of platelets against active smokers and passive smokers in students of the Polytechnic Medica Farma Husada Mataram 2021. The sample of this study was the blood of students who smoked as active and passive smokers. The method used is the direct method (Rees Ecker) with units of thousand/mm3. The results showed an increase in platelet count in active smokers to 211,500/mm3 and a decrease in platelet count in passive smokers by 130,750/mm3. Thus, there is a quantitative difference in the number of platelets in active smokers and passive smokers in college students.